Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s12978-015-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Expanding availability of safe abortion services through private sector accreditation: a case study of the Yukti Yojana program in Bihar, India

Abstract: BackgroundRecognizing the need to increase access to safe abortion services to reduce maternal mortality and morbidity, the state government of Bihar, India introduced an innovative mechanism of accrediting private health care facilities. The program, Yukti Yojana (‘a scheme for solution’), accredits eligible health facilities and supports them in providing abortion-related services free of charge to rural and low-income urban women. This paper describes implementation of Yukti Yojana.MethodsA descriptive anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…In two studies, the authors did not specify the intervention’s success. Only four studies reporting specific interventions were assessed as being strong quality ( n = 1) [ 34 ] or moderate quality ( n = 3) [ 35 , 36 ]. Additional details of specific intervention studies appear in Additional File 1 and in the thematic analyses below.…”
Section: Resultsmentioning
confidence: 99%
“…In two studies, the authors did not specify the intervention’s success. Only four studies reporting specific interventions were assessed as being strong quality ( n = 1) [ 34 ] or moderate quality ( n = 3) [ 35 , 36 ]. Additional details of specific intervention studies appear in Additional File 1 and in the thematic analyses below.…”
Section: Resultsmentioning
confidence: 99%
“…Private facilities are required to have either a qualified gynaecologist or a doctor trained to provide abortion, as well as a functioning labour room and operating theatre. There were 49 such private facilities accredited under the Yukti program across Bihar ( 33 ); although the location of these facilities is not reported, it is very likely that most are in urban centres. Over an 18-month period 10,700 women were provided abortion care, two thirds of whom were rural ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…There were 49 such private facilities accredited under the Yukti program across Bihar ( 33 ); although the location of these facilities is not reported, it is very likely that most are in urban centres. Over an 18-month period 10,700 women were provided abortion care, two thirds of whom were rural ( 33 ). However, in large areas of our study districts in MP (even in one whole district), there was no private facility providing abortion services; therefore, the public sector is the major provider.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several articles describe specific difficulties in guaranteeing equitable access to services in South Africa, Zambia, and India, and the interventions designed to address these problems. [9][10][11] Comprehensive reviews of a single country's program, including health system level implementation steps, successes, and difficulties exist for India, 12 Mexico City, 13 and South Africa, 14 but there are no comparative data to guide future program implementation. A recent five-country case study developed to inform the WHO guideline on task sharing found limited documentation of the implementation processes undertaken.…”
Section: Andmentioning
confidence: 99%
“…One multicountry report did offer a framework for the successful implementation of abortion services; it relied primarily on a review of published and “grey” literature although it included some interviews with key informants . Several articles describe specific difficulties in guaranteeing equitable access to services in South Africa, Zambia, and India, and the interventions designed to address these problems . Comprehensive reviews of a single country's program, including health system level implementation steps, successes, and difficulties exist for India, Mexico City, and South Africa, but there are no comparative data to guide future program implementation.…”
Section: Introductionmentioning
confidence: 99%